Design a new hybrid controller based on an improvement version of grey wolf optimization for trajectory tracking of wheeled mobile robot - Hussein Rasha Mohammed (FME Transactions, 2023)
Nonholonomic wheeled mobile robots are considered to be multi-input multi-output systems that are performed in varying environments. This work presents the trajectory tracking control of a nonholonomic wheeled mobile robot (WMR). The Kinematic and the dynamic models of the robot were derived. A new hybrid controller was designed, which consisted of two controllers based on an optimization algorithm to solve the trajectory tracking problem. The first controller is the Fractional order PID controller, which is based on the kinematic model and has been applied to control the linear and the angular robot velocities, while the second controller is a linear quadratic regulator (LQR) and is based on the dynamic model used to control the motors' torques. A new, improved version of grey wolf optimization wasadopted to tune the parameters of the hybrid controller. The main goals of this improvement are rapid convergence towards a solution, reducing the effect of the wolves' random motion, and balancing exploitation and exploration processes. MATLAB software was used to simulate the results under an S-shape trajectory and to evaluate the robustness and performance of the proposed control unit. The simulation results demonstrated the adopted control system's activity and efficiency based on the mean square error (MSE) between the desired and actual trajectory. The values of MSE of trajectory in the X and Y directions and the orientation are [6.589*10-4(m) 8.421*10-5(m) 0.00401(rad)]T . Also, the adopted control system can generate smooth values of the control input signals without sharp spikes. The performance of the presented control system has been verified and compared with the results obtained from the other two control systems, and the simulation results have offered the superiority and effectiveness of the hybrid controller of this work.